2017
DOI: 10.22159/ijpps.2017v9i2.16021
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Growth Inhibitory Effect of Flavonol–kaempferol and Conventional Chemotherapeutic Drugs on Cancer Cells

Abstract: Objective: The objective of the present study was to evaluate synergistic growth inhibitory effect of a flavonol, kaempferol in combination with chemotherapeutic drugs doxorubicin or cisplatin. Methods:The anti-proliferative activities of kaempferol, doxorubicin and cisplatin on human colorectal cancer cells (HCT-15) and human breast cancer (MDA MB 231) were analyzed by 3-(4,5-dimehylthiaol-2-yl)-2,5-diphenyltetraolium bromide (MTT) assay. Further, combinational studies were performed in both the cell lines to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Different molecular mechanisms are involved in DIC which is multifactorial and complex, include direct DNA damage, formation of free reactive oxygen radicals, interference with DNA repair, alterations of cellular calcium homeostasis, mitochondria injury, lysosomal changes, and apoptosis [4,5]. The heart is particularly sensitive to the oxidative damage due to low levels of antioxidant enzymes, large density of mitochondrial, and high rate of oxygen consumption [6].…”
Section: Introductionmentioning
confidence: 99%
“…Different molecular mechanisms are involved in DIC which is multifactorial and complex, include direct DNA damage, formation of free reactive oxygen radicals, interference with DNA repair, alterations of cellular calcium homeostasis, mitochondria injury, lysosomal changes, and apoptosis [4,5]. The heart is particularly sensitive to the oxidative damage due to low levels of antioxidant enzymes, large density of mitochondrial, and high rate of oxygen consumption [6].…”
Section: Introductionmentioning
confidence: 99%
“…The research presents the findings of kaempferol-cisplatin-doxorubicin combo investigations. The results demonstrated a substantial synergistic therapeutic benefit when doxorubicin or cisplatin was used in conjunction with kaempferol in HCT-15 and MDA-MB-231 cell lines [ 137 ].…”
Section: Anti-cancer Activities Of Kaempferol In Literature Cancer Typesmentioning
confidence: 99%
“…Studies have shown that Kaempferol may participate in the ERK (extracellular signal-regulated kinase)-dependent MAPK pathway to reduce Dox-induced cardiac toxicity by inhibiting p53-mediated mitochondrial-dependent intrinsic apoptotic signaling [ 51 ]. A recent study showed that Kaempferol combined with Dox or cisplatin has a strong synergistic therapeutic effect on HCT-15 and MDA-MB-231 cells [ 50 ].…”
Section: Small Molecules That Attenuate Dox-induced Cardiotoxicitymentioning
confidence: 99%